2016
DOI: 10.1177/1099800416653184
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Metabolic Syndrome in People With Schizophrenia in Inpatient Rehabilitation Wards

Abstract: In this study, the prevalence of MetS was higher than that reported for patients utilizing community-based services in Taiwan. The important risk factors for MetS were being overweight and older than 40. The protective factors for MetS were a high HPLP-exercise score and leisure-based physical activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
4
7
0
1
Order By: Relevance
“…Compared to the results of those two studies, the prevalence of metabolic syndrome among these community-dwelling schizophrenia patients was twice as high as that of the general population. Furthermore, the prevalence observed in this study was higher than has been observed in Japan (34.2%) [ 36 ], Taiwan (37.8%) [ 37 ], and Iran (23.9%) [ 38 ], which confirms the need for proactive management of metabolic syndrome in people with schizophrenia in Korea. Therefore, mental health care nurses who manage the health of people with schizophrenia living in the community need to recognize the high prevalence of metabolic syndrome among their patients and implement regular education and management.…”
Section: Discussionsupporting
confidence: 67%
“…Compared to the results of those two studies, the prevalence of metabolic syndrome among these community-dwelling schizophrenia patients was twice as high as that of the general population. Furthermore, the prevalence observed in this study was higher than has been observed in Japan (34.2%) [ 36 ], Taiwan (37.8%) [ 37 ], and Iran (23.9%) [ 38 ], which confirms the need for proactive management of metabolic syndrome in people with schizophrenia in Korea. Therefore, mental health care nurses who manage the health of people with schizophrenia living in the community need to recognize the high prevalence of metabolic syndrome among their patients and implement regular education and management.…”
Section: Discussionsupporting
confidence: 67%
“…Separate studies conducted in Korea and Taiwan compare a cohort of patients with schizophrenia with the general population, revealing a high prevalence of MetS in the first group, which is consistent with data from European studies (22,23). However, to date, few comparisons have been made between individual subpopulations of patients with schizophrenia.…”
Section: Introductionsupporting
confidence: 75%
“…Three studies reported male gender to be associated with MetS (46, 74, 76), while four studies found female gender to be a risk factor for MetS (54,71,89,91). Several studies reported a higher age of patients treated with antipsychotics to be significantly associated with the development of MetS (43,46,55,73,74,85,87,91). Grover et al (71), found age >35 to be associated with MetS.…”
Section: Pooled Results Of Sgasmentioning
confidence: 99%